Evolving the Promiscuity of Elizabethkingia meningoseptica Oleate Hydratase for the Regio‐ and Stereoselective Hydration of Oleic Acid Derivatives. Issue 22 (17th April 2019) - Engleder, Matthias; Strohmeier, Gernot A.; Weber, Hansjörg; Steinkellner, Georg; Leitner, Erich; Müller, Monika; Mink, Daniel; Schürmann, Martin; Gruber, Karl; Pichler, Harald
Abstract: The addition of water to non‐activated carbon–carbon double bonds catalyzed by fatty acid hydratases (FAHYs) allows for highly regio‐ and stereoselective oxyfunctionalization of renewable oil feedstock. So far, the applicability of FAHYs has been limited to free fatty acids, mainly owing to the requirement of a carboxylate function for substrate recognition and binding. Herein, we describe for the first time the hydration of oleic acid (OA) derivatives lacking this free carboxylate by the oleate hydratase from Elizabethkingia meningoseptica (OhyA). Molecular docking of OA to the OhyA 3D‐structure and a sequence alignment uncovered conserved amino acid residues at the entrance of the substrate channel as target positions for enzyme engineering. Exchange of selected amino acids gave rise to OhyA variants which showed up to an 18‐fold improved conversion of OA derivatives, while retaining the excellent regio‐ and stereoselectivity in the olefin hydration reaction. Abstract : Redefining the substrate spectrum : The highly regio‐ and stereoselective hydration of oleic acid derivatives by an oleate hydratase is possible. The carboxylate of a free fatty acid—previously considered essential—is not mandatory for the conversion, which thus expands hydration biocatalysis beyond inferred restrictions.